Some reflections on the Silala: The case of chile against Bolivia before the International Court of Justice - Antialón Conde, Alexander (2022)
After the written and oral phase of the dispute over the status and use of the waters of the Silala between Chile and Bolivia, before the International Court of Justice (ICJ), the Court will now deliberate and promptly notify the parties for the issuance of the sentence.In this context, this essay will make known the claims of the States in dispute, analyzing the main issues on which the Court will have to rule and offer some conclusions.